Kualitas Produk, Kualitas Pelayanan, dan Lokasi Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervening: (Studi Kasus pada PT. Putra Indo Mandiri Sejahtera (PT. PIMS)/ Gundaling Farm) - Sipayung, Rizki (Politeknik Cendana, 2022)
Along with the times and the level of activity of the higher work activities, people need attractions that could be of interest to unwind after a tired work. Attraction which also provide food or beverages typically have a special attraction for the public. PT. Indo Putra Mandiri Sejahtera (PIMS) is a company engaged in the production of milk which is located in an area attraction Berastagi. To still be able to maintain and gain a loyal customer PT. Indo Putra Mandiri Sejahtera (PIMS) Hattush strategize more accurate as improve product quality, service quality, and location of the company to be able to satisfy its customers. The purpose of this study was to determine and analyze the effect of product quality, service quality, customer loyalty terhapap company's location directly and indirectly, that is through customer satisfaction. This research is descriptive statistics and the nature of the research is descriptive explanatory. Methods of data collection is by interview (interview), a list of questions (questionare) and documentation study. The population in this study as many as 287 840 people who make a purchase at. PIMS (Indo Mandiri Putra Sejahtera / Gundaling Farm). With the sampling technique used is accidental sampling the samples in this study of 100 people. Scale measurements using an interval scale and analysis techniques were used that path analysis (path analysis) as well as using residual test against intervening variables. The first research results show substructures product quality, service quality, the company's locations simultaneously positive and significant impact on customer satisfaction at PT. Indo Putra Mandiri Sejahtera with a coefficient of determination (R2) of 0.777 or 77.7%. Partially product quality, service quality, corporate locations and a significant positive effect on customer satisfaction. The results of the second substructure studies show the product quality, service quality, corporate locations and customer satisfaction positive and significant impact on customer loyalty PT. Indo Putra Mandiri Sejahtera with a coefficient of determination (R2) of 0.327 or 32.7%. Partially quality products and locations having an positive and significant impact on customer loyalty. Quality of service and customer satisfaction not significant effect on loyalty to the PT. Indo Putra Sejahtera Mandiri. Customer satisfaction is not an intervening variable influence product quality, service quality, the location of the company on customer loyalty.